Cognitive dissonance as a reason for low perceived HIV risk among Black women - Mandy J. Hill (Frontiers in Sociology)
Existing HIV-related literature affirms that Black women in the US have a low perceived risk of HIV. Yet, Black women consistently experience higher HIV incidence than other women. The ability of HIV risk perception to influence HIV prevention behaviors remains unclear. Lack of knowledge is often described as the primary driver of a low perceived risk of contracting HIV. What if the primary driver is not lack of knowledge? Instead, it is possible and even likely, that cognitive dissonance became a commonly used coping strategy for survival among Black women whose social standing hinges, in part, on the independent ability to maintain romantic partnerships while doubling in purpose as a primary driver for low perceived risk of HIV. The three key points of this commentary are that underpinnings of low perceived risk of HIV among Black women exist, cognitive dissonance is a likely byproduct of reconciling cultural norms with self-identity, and there is a permanence in disconnect between actual and perceived risk of HIV among Black women. To achieve sexual health equity, researchers must enhance awareness into the nuanced reasons that low perceived risk of HIV persist.